Population and Target Population in Research Methodology - Willie, Michael Mncedisi (Golden Ratio of Social Science and Education, 2024)
This paper thoroughly explores the foundational principles governing population and target population concepts within research methodology. It delves into the essential roles these concepts play in shaping the design and influencing the interpretation of research studies. Through an exhaustive analysis, it meticulously outlines the nuances that differentiate these two concepts, elucidating their respective contributions and implications across diverse research paradigms. Moreover, this paper underscores the importance of establishing clear definitions and boundaries for both the population and the target population. It emphasises how such precision is indispensable in guiding the formulation of effective sampling strategies, which are pivotal for ensuring the accuracy and reliability of study outcomes. Furthermore, it sheds light on how the clarity in defining these concepts significantly impacts the generalizability of research findings, elucidating how findings derived from a well-defined target population can be more confidently extrapolated to broader populations. In addition to methodological considerations, this paper investigates the ethical dimensions inherent in delineating population and target population. It underscores the moral imperative of accurately representing the groups under study, particularly ensuring equitable access to research participation and safeguarding against potential biases.